2020
DOI: 10.1021/acs.jafc.0c06249
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of the Metabolome and Transcriptome of Sorghum bicolor Reveals Dynamic Changes in Flavonoids Accumulation under Saline–Alkali Stress

Abstract: With the perpetuation of soil salinization, it is imperative to improve the salt and alkaline tolerance of crops. Sorghum bicolor, a C4 crop, is often grown in semiarid areas due to its high tolerance of various abiotic stresses. Whether to improve the resistance of the sorghum itself or that of other crops, it is necessary to understand the response of sorghum under saline–alkali stress. An integrative analysis of the metabolome and transcriptome of sorghum under normal conditions and treatments of moderate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 41 publications
4
35
0
Order By: Relevance
“…Our previous studies also explored dozens of DEGs related to salt tolerance in other sorghum genotypes planted in salt environments based on transcriptomic technology ( Cui et al, 2018 ). Although the salt stress condition is different, the outcomes of our study showed similarities from previous studies by Ma et al (2020) . Ma et al (2020) found that anthocyanin biosynthesis-related genes such as LOC8074150 which editing anthocyanidin synthase were up-regulated under moderate salt−alkali stress.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our previous studies also explored dozens of DEGs related to salt tolerance in other sorghum genotypes planted in salt environments based on transcriptomic technology ( Cui et al, 2018 ). Although the salt stress condition is different, the outcomes of our study showed similarities from previous studies by Ma et al (2020) . Ma et al (2020) found that anthocyanin biosynthesis-related genes such as LOC8074150 which editing anthocyanidin synthase were up-regulated under moderate salt−alkali stress.…”
Section: Discussionsupporting
confidence: 78%
“…Although the salt stress condition is different, the outcomes of our study showed similarities from previous studies by Ma et al (2020) . Ma et al (2020) found that anthocyanin biosynthesis-related genes such as LOC8074150 which editing anthocyanidin synthase were up-regulated under moderate salt−alkali stress. In our work, the comparative analysis using RNA-Sequence revealed that a lot of the DEGs were located in the flavonoid biosynthesis pathway, indicating flavonoid may potentially confer protection against salt stress ( Figure 3A ).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The total phenolic content and antioxidant activity of pomegranate fruit with severe sunburn were lower than those of undamaged fruit [ 14 ]. This mechanism can also be expanded to other stress [ 25 ] and antioxidants [ 26 ].…”
Section: Discussionmentioning
confidence: 99%